2016
DOI: 10.1080/14703297.2016.1260490
|View full text |Cite
|
Sign up to set email alerts
|

Fostering first-year student learning through research integration into teaching: Student perceptions, beliefs about the value of research and student achievement

Abstract: Research should be explicated in undergraduate teaching in a way that stimulates student learning. Previous studies in higher education have shown that student perceptions of research integrated into teaching could promote student learning, but have also indicated that it can be difficult to confront first-year undergraduates with research during courses. In this study, we describe relationships between first-year medical student perceptions of research, learning outcomes and beliefs about the value of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
0
30
0
5
Order By: Relevance
“…Items on the research self-efficacy scale were self-developed and designed based on the previous two efficacy scales, but more specifically addressing self-efficacy regarding research. Perceptions of research were examined by using the subscale from the Student Perception of Research Integration Questionnaire (SPRIQ) focusing on students’ beliefs about the value of research and learning [ 42 ]. Curiosity was measured with the Epistemic Curiosity Scale, divided in items on interest and deprivation curiosity [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Items on the research self-efficacy scale were self-developed and designed based on the previous two efficacy scales, but more specifically addressing self-efficacy regarding research. Perceptions of research were examined by using the subscale from the Student Perception of Research Integration Questionnaire (SPRIQ) focusing on students’ beliefs about the value of research and learning [ 42 ]. Curiosity was measured with the Epistemic Curiosity Scale, divided in items on interest and deprivation curiosity [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Student perceptions of research in teaching can promote various learning outcomes such as research dispositions, research skills and student achievement (Vereijken, van der Rijst, de Beaufort, van Driel, & Dekker, 2018;Visser-Wijnveen, van Driel, van der Rijst, Visser, & Verloop, 2012). Undergraduates can perceive both benefits and disadvantages of research integrated into teaching (Healey, Jordan, Pell, & Short, 2010).…”
Section: Students Perceptions and Beliefsmentioning
confidence: 99%
“…To study undergraduate student perceptions of research in teaching we administered a version of the Student Perception of Research Integration Questionnaire (SPRIQ) in which the item wording was adjusted to medical education (Vereijken et al, 2018;Visser-Wijnveen et al, 2016). The scales included student perceptions of teaching through (1) critical reflection on the way research findings are produced; (2) student research participation;…”
Section: Instrument and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPRIQ scores of the current study were similar to the mean scores of 2.44 to 3.75 reported by Veriijken, van der Rijst, van Driel, and Dekke (2018), who studied research perceptions of first-year medical students. Findings from another study that used the SPRIQ found that student motivation for research is strongly related to merging current research into teaching and that student beliefs about research are related to achievement (Vereijken, van der Rijst, de Beaufort, van Driel, & Dekker, 2018).…”
Section: Discussionmentioning
confidence: 99%